Effect of age on the conversion of 25-hydroxyvitamin D3 to 1,25-dihydroxyvitamin D3 by kidney of rat. - Armbrecht, H J; Zenser, T V; Davis, B B (The Journal of Clinical Investigation, 1980)
The decreased absorption of calcium by the small intestine of the adult may reflect changes in vitamin D metabolism with age. The purpose of this study was to compare the capacity of young (1.5 mo of age) and adult (12 mo of age) vitamin D-deficient rats to convert 25-hydroxyvitamin D to 1,25-dihydroxyvitamin D, the physiologically active form of vitamin D. Young rats responded to an oral dose of 25-hydroxyvitamin D3 with significantly increased intestinal absorption of calcium and a three-fold increase in the intestinal content of vitamin D-stimulated calcium-binding protein. Adult rats showed no significant increase in these parameters. The conversion of 25-hydroxyvitamin D3 to 1,25-dihydroxyvitamin D3 was measured in the whole animal by administering a dose of tritiated 25-hydroxyvitamin D3 and determining the appearance of tritiated metabolites in plasma and small intestine. In the adult rat, only 2.1 +/- 0.6% of the plasma radioactivity was in the form of 1,25-dihydroxyvitamin D3 after 24 h compared with 20.8 +/- 3.0% in the young. The conversion of tritiated 25-hydroxyvitamin D3 to its products was also measured directly in isolated slices of renal cortex. 1,25-Dihydroxyvitamin D3 production by adult renal slices was found to be less than one-tenth that of slices from the young. These results indicate that there is a marked decrease in the capacity of the vitamin D-deficient adult rat to convert 25-hydroxyvitamin D3 to 1,25-dihydroxyvitamin D3. This is probably due to the decreased capacity of the adult kidney to 1-hydroxylate 25-hydroxyvitamin D3. These studies also demonstrate the usefulness of renal slices in measuring changes in the renal conversion of 25-hydroxyvitamin D3 to 1,25-dihydroxyvitamin D3 in the mammal.